An Overview about Adverse Hepatic Effects of the Plants Used in Turkey - Gürbüz, Perihan (Cerrahpaşa Medical Journal, 2020)
Herbal supplements are widely used for improving health and treating diseases in nearly all cultures of the world. However, the efficacy, safety, and drug interactions of many of the herbal treatment modalities are not known scientifically, and they are generally used without professional health assistance. Injudicious plant usage has been shown to be a risk factor for serious and unexpected side effects, and from this perspective, herbal drug usage is related to 25%–30% of drug-induced liver injury cases. Plant usage as an alternative therapeutic modality is common in Turkey. In this study, the adverse hepatic effects of the commonly used plants in Turkey has been reviewed. More than 400 plants that are sold by herbalists in different regions of Turkey have been obtained from various studies on this topic, and these plants were investigated for their hepatic effects in PubMed and Science Direct databases. The adverse hepatic outcomes of 27 of the researched plants. Studies about plant hepatotoxicity, plant-plant interaction, and plant-drug interaction have been reviewed in this article. Herbal modalities are widely used as an alternative and complementary treatment method in the population; however, the basic hepatotoxic compounds and the liver injury mechanism of many of the frequently used plants and the molecular action mechanism of most of the ingredient compounds of the plants are not exactly known. Multidisciplinary studies on the mentioned topics will be helpful in understanding the role of plants and hepatotoxicity in medical approaches. Cite this article as: Gürbüz P. An Overview about Adverse Hepatic Effects of the Plants Used in Turkey. Cerrahpaşa Med J 2020; 44(3): 115-124.